Analisis Kompetensi Menulis Karya Tulis Ilmiah Mahasiswa di Indonesia - Muhammad Heriyudananta (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
This study aimed to determine the competence of writing student scientific papers in Indonesia and its factors. This research is a type of library research (library research). The data sources that are the study of this research are books, scientific articles from journals, papers, magazines, and so on, which are relevant to this study and can answer the main problem. At the same time, the approach used in this research is philosophical. While the data collection technique used is documentation. In order to direct the accuracy and accuracy of the data under study, the analysis method used is content analysis. The findings of this study indicate that the competence of Indonesian students in writing scientific papers is still very low. In writing, most of them do not heed the guidelines and rules of writing scientific papers, and the level of plagiarism is very high. Based on the research results, the most challenging problems students face in writing scientific papers are difficulties in obtaining references and not knowing writing techniques. Meanwhile, the factors that cause difficulties in writing scientific papers are, for example, low motivation of students in writing, lack of self-confidence and lack of mood, low reading interest, low student curiosity, and students' understanding of scientific writing that is not good as well as low mastery, against his writing conventions.